THE IMPORTANCE OF FINANCIAL MATHEMATICAL ELEMENTS IN REAL ESTATE VALUATION - Raximov Zafar Odilovich; Ismailov Najmiddin Ilxamovich (Central Asian Journal of Theoretical and Applied Science, 2022)
In this work elements of financial mathematics are considered, six functions over of compound interests are given, which is estimations cost of the real estate. The usage of financial mathematics functions in the practice of estimation of cost of objects of the real estate promotes its validity, and also efficiency of making decision on investing in the real estate.